2020
DOI: 10.1002/jbm.b.34568
|View full text |Cite
|
Sign up to set email alerts
|

Covalent attachment of resveratrol to stainless steel toward the development of a resveratrol‐releasing bare‐metal stent

Abstract: Herein, we describe the covalent attachment of resveratrol, a naturally occurring antioxidant, to the surface of stainless-steel as a model for designing a novel bare-metal stent to treat coronary artery disease. Resveratrol has been shown to reduce oxidative stress in dysfunctional endothelial cells, and stimulate arterial healing. Resveratrol treatments, however, are limited by low water solubility, such that a localized delivery to the site of arterial narrowing via a coated stent presents a promising strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In vitro and in vivo studies with orally administered resveratrol have shown that resveratrol increases eNOS expression and activity, enhances NO production, prevents eNOS uncoupling, and reduces endothelial oxidative stress [ 16 , 30 , 31 ]. In another study with a focus on the development of a drug coated stent, resveratrol was covalently attached to a stainless-steel surface [ 32 ]. It could be shown that endothelial cells grown on surface-bound resveratrol released higher amounts of nitric oxide compared to cells grown on unmodified stainless steel [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo studies with orally administered resveratrol have shown that resveratrol increases eNOS expression and activity, enhances NO production, prevents eNOS uncoupling, and reduces endothelial oxidative stress [ 16 , 30 , 31 ]. In another study with a focus on the development of a drug coated stent, resveratrol was covalently attached to a stainless-steel surface [ 32 ]. It could be shown that endothelial cells grown on surface-bound resveratrol released higher amounts of nitric oxide compared to cells grown on unmodified stainless steel [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study with a focus on the development of a drug coated stent, resveratrol was covalently attached to a stainless-steel surface [ 32 ]. It could be shown that endothelial cells grown on surface-bound resveratrol released higher amounts of nitric oxide compared to cells grown on unmodified stainless steel [ 32 ].…”
Section: Discussionmentioning
confidence: 99%